B Assessment of valvular calcification and inflammation by positron emission tomography. (16th May 2012) - Dweck, M R; Jones, C; Joshi, N; White, A; Fletcher, A M; Richardson, H; McKillop, G; van Beek, E J R; Boon, N A; Rudd, J H F; Newby, D E
Abstract : Background: The pathophysiology of aortic stenosis is incompletely understood and the relative contributions of valvular calcification and inflammation to disease progression are unknown. Methods: Patients with aortic sclerosis and mild, moderate and severe stenosis were prospectively compared to age and sex-matched control subjects. Aortic valve severity was determined by echocardiography. Calcification and inflammation in the aortic valve were assessed by sodium 18-fluoride (18F-NaF) and 18-fluorodeoxyglucose (18F-FDG) uptake using positron emission tomography. Histological analysis was performed on the valves of five patients who subsequently underwent aortic valve replacement. Results: 121 subjects (20 controls; 20 aortic sclerosis; 25 mild, 33 moderate and 23 severe aortic stenosis) were administered both 18F-NaF and 18F-FDG. Quantification of tracer uptake within the valve demonstrated excellent inter-observer repeatability with no fixed or proportional biases and limits of agreement of ±0.21 (18F-NaF) and ±0.13 (18F-FDG) for maximum tissue-to-background ratios. Activity of both tracers was higher in patients with aortic stenosis than control subjects (18F-NaF: 2.87±0.82 vs 1.55±0.17; 18F-FDG: 1.58±0.21 vs 1.30±0.13; both p<0.001). 18F-NaF uptake displayed a progressive rise with valve severity (r 2 =0.540, p<0.001) and colocalised to osteocalcin staining on histology. Uptake was observed both in the presence and absence of underlying calcium on CT with the latter predominating. 18F-FDG displayed a more modest increase in activity with valve severity (r 2 =0.218; p<0.001) and mapped to areas of macrophage accumulation. Among patients with aortic stenosis, 91% had increased 18F-NaF (>1.97) and 35% increased 18F-FDG (>1.63) uptake. A weak correlation between the activities of these tracers was observed (r 2 =0.174, p<0.001) and while 18F-NaF activity was higher in the aortic valve than aortic atheroma (2.68±0.84 vs 2.07±0.30; p<0.001) the reverse was true for 18F-FDG (1.56±0.21 vs 1.80±0.25; p<0.001). Conclusions: Positron emission tomography is a novel, feasible and repeatable approach to the evaluation of valvular calcification and inflammation in patients with aortic stenosis. Calcification appears to be the predominant process that is particular to the valve and disproportionate to the degree of inflammation, indicating it to be a more attractive target for therapeutic intervention.